A salvação pela eugenia: a crítica habermasiana à eugenia liberal e suas controvérsias - Sousa, Alberto Marques de (2013)
The argumentative strategy of Jürgen Habermas against liberal eugenics has provoked many different reactions among several thinkers, establishing important debates and discussions among those who advocate greater control of scientific research and those who plead for greater freedom of action with regard to the intervention of human nature. Our search in this work, in the light of the philosophy of science and its advancements, walks toward understanding these debates and discussions, as well as the understanding of the reality of genetic research and its application today, that leads to the creation of a new religion, the eugenic religion of beings. Habermas in his work Die Zukunft of menschlichen Natur brings us to the realization that eugenics is still ongoing, but in new clothes and old arguments that put this question in the center of the debate of science and also of the Religious Sciences. While in the past the eugenic project distinguished people by their race, intellectual development and skills to practical activities, today's proposal of liberal eugenics is free to choose the opportunity to maximize the control of the individuals capabilities with a dialogue grounded in utilitarian philosophy, specifically the gain of quality of life, which is increasing pleasure and decreasing pain